Optimum taxation of inheritances - Johann K. Brunner; Susanne Pech (Johannes Kepler University of Linz, Department of Economics, 2008)
We incorporate the fact that inheritances create a second distinguishing characteristic of individuals, in addition to earning abilities, into an optimum income taxation model with bequests motivated by joy of giving. We show that a tax on inheritances and a uniform tax on all expenditures including bequests are equivalent and that either is desirable, according to an intertemporal social objective, if on average high-able individuals have larger inherited endowments than low-able. We demonstrate that such a situation results as the outcome of a process with stochastic transition of abilities over generations, if all descendants are more probable to have their parents ability rank than any other.
Keywords: H21; H24; 330; inheritance tax; Erbschaftsteuer; Optimale Besteuerung; Theorie